Information and communication ensuring of activity of bodies of state power: theoretical aspects - J. N. Shestun; P. I. Ananchenkova (Путеводитель предпринимателя, 2020)
The article considers specific features of communication in the system of government. The authors concluded that the ability of public relations can be used to enhance the openness of state and municipal administration closer to the citizens’ interests. The closeness of controls, insufficient or ineffective interaction with the public leads to alienation of people from power, which can be a prerequisite of social upheaval.